2015
DOI: 10.1093/molbev/msv007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Balancing Selection in LAD1 Maintains a Missense Trans-Species Polymorphism in Humans, Chimpanzees, and Bonobos

Abstract: Balancing selection maintains advantageous genetic and phenotypic diversity in populations. When selection acts for long evolutionary periods selected polymorphisms may survive species splits and segregate in present-day populations of different species. Here, we investigate the role of long-term balancing selection in the evolution of protein-coding sequences in the Homo-Pan clade. We sequenced the exome of 20 humans, 20 chimpanzees, and 20 bonobos and detected eight coding trans-species polymorphisms (trSNPs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 63 publications
2
69
0
Order By: Relevance
“…; Teixeira et al . ). These studies have been particularly comprehensive, as they investigated signatures of BS acting at various temporal scales.…”
Section: Evidence For Balancing Selection In Naturementioning
confidence: 97%
“…; Teixeira et al . ). These studies have been particularly comprehensive, as they investigated signatures of BS acting at various temporal scales.…”
Section: Evidence For Balancing Selection In Naturementioning
confidence: 97%
“…In some cases, incomplete lineage sorting occurs as a result of balancing selection maintaining polymorphisms: when speciation occurs, both daughter species may maintain the same “trans‐specific” polymorphisms, even though with recombination, the signal of ancestral origin may erode over time . Good examples of shared polymorphisms between humans and apes are MHC and ABO blood group loci , among other genes. In the species complex including the major mosquito vector, Anopheles gambiae , a very large chromosomal inversion, 2La (22 Mb in length, 8.5% of the total genome size) is maintained as a balanced polymorphism that has persisted across several speciation events .…”
Section: What Causes Phylogenetic Incongruence In Eukaryotes?mentioning
confidence: 99%
“…Several studies searching for the occurrence of trans-species polymorphism have shown that advantageous variants in the human population may have been inherited from distant ancestral species [142145]. For example, functional diversity in ABO blood group has been maintained across primates for millions of years, probably due to host–pathogen coevolution [142].…”
Section: Favoring Advantageous Variants To Increase Adaptationmentioning
confidence: 99%